Dual-Server Authenticated-Encryption in Cloud Computing - Swapneel Niraj Deo, Mrs. R. Mangalagowri, Satyam Singh (International Journal of Advanced Science and Technology, 2020)
While trying to store data in cloud, the problem arises when we try to find important data with efficiency and reliability. Approach to search with the help of encryption gives us a reliable way to avoid data leakage and privacy. (PEKS) “Public-key encryption with keyword search” is an important area of study. Although PEKS might be a promising area of study, most of its classifications can’t prevent Internal keyword guessing attack. This is what we will try to avoid in future. In the previous years, the approach to avoid internal keyword guessing attacks have failed to give efficiency and reliability. Taking in account the listed complications, we introduce (DPAEKS) “Dual-server Public-key Authenticated Encryption with Keyword Search”, which prevents internal keyword guessing attack with the help of two different servers which agrees with the verification property and counteract. Also, we introduce nonlinear pairs to build DPAEKS. Outcomes of testing our strategy on daily-life sets of data tells us that our strategy provides efficiency and great reliability and is eligible to perform over a wide range of empirical applications. Keywords: component, public-key encryption with keyword search, dual server, inside keyword guessing attacks.